Goddess Ganga and a Dvarapala on the Garbhagriha doorjamb - Temples of India Project Team (Jio Institute, 2024)
The bottom of the garbhagriha (sanctum sanctorum) door frame is decorated with the figures of the river Goddess and dvarapalas (door guardians). On the proper right side of the doorframe, the river Goddess Ganga is represented. The Goddess is shown standing on a pedestal with her vahana (mount), a makara (crocodile), depicted behind the pedestal. She is heavily bejewelled and has a canopy of inverted flowers. Next to her stands a four-armed dvarapala, with all arms broken. He has a beard and his jatas (matted hair) are neatly arranged in layers, and his two attendants are depicted alongside him. At the bottom, a niche is carved which is installed with the figure of Ganesha.